EFFECTIVENESS OF THE DISCOVERY LEARNING MODEL ASSISTED BY PINTAR MEDIA (PAPAN INTERAKTIF BANGUN DATAR) ON THE MATHEMATICAL LITERACY SKILLS OF ELEMENTARY SCHOOL STUDENTS - Noor Faizul Muna; Milati Azka; Nazula Tamami Layalia; Aldise Anggi Marta Dwi; Fitriyah Amaliyah (UIR PRESS, 2025)
This study aims to determine the effectiveness of the discovery learning model assisted by PINTAR media (Papan Interaktif Bangun Datar) on the mathematical literacy skills of elementary school students in comparing the characteristics of plane shapes. The research used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The population consisted of all fifth-grade students of SD 3 Gondosari. The sample included 11 students, consisting of 6 female and five male students, selected using a saturated sampling technique. The research instruments included pretest and posttest questions to measure students' mathematical literacy. Data analysis techniques used tests of normality, Paired Sample Test, and the N-Gain Test to determine the effectiveness of the discovery learning model assisted by PINTAR media (Papan Interaktif Bangun Datar) on mathematical literacy skills in comparing the characteristics of plane shapes. The results showed improved students' mathematical literacy skills after implementing the discovery learning model assisted by PINTAR media. This is evidenced by an increase in the average score from 45.36 to 67.36 after using PINTAR media. T Test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest results.